Kinematic accuracy and dynamic performance of a simple planar space deployable mechanism with joint clearance considering parameter uncertainty. (July 2017) - Li, Junlan; Huang, Hongzhou; Yan, Shaoze; Yang, Yunqiang
Abstract: Joint clearance and the uncertainty of geometric and physical parameters significantly influence the kinematic accuracy and dynamic response of space deployable mechanisms. Such mechanisms have been widely employed in astronautic missions to improve the capabilities of launchers. This paper proposes a methodology to investigate the kinematic accuracy and dynamic performance of space deployable mechanism with joint clearance while considering parameter uncertainty. The model of space deployable mechanism with a planar revolute joint is provided. With consideration of several uncertain parameters, the solving procedure of the dynamic equations is presented based on the Monte Carlo method. A case study is conducted to reveal the effect of parameter uncertainty on its kinematic accuracy and dynamic performance. The results indicate that parameter uncertainty should be considered to accurately evaluate the performance of long-term operating space deployable mechanisms, especially for such systems with clearance joints. According to the results, brief suggestions for design and evaluation of the mechanisms are provided. Highlights: A dynamic model of a typical space deployable mechanism with joint clearance is presented. Uncertain parameters are considered in the dynamic model. The effect of parameter uncertainty on the kinematic accuracy is investigated. The dynamic performance is discussed considering parameter uncertainty.